Peeling the Otolith of Fish: Optimal Parameterization for Micro-CT Scanning - Vasconcelos-Filho, Jonas E.; Thomsen, Felix S. L.; Stosic, Borko; Antonino, Antonio C. D.; Duarte, Daniel A.; Heck, Richard J.; Lessa, Rosangela P. T.; Santana, Francisco M.; Ferreira, Beatrice P.; Duarte-Neto, Paulo J. (Frontiers in Marine Science, 2019)
In this paper, we aim to provide optimal parameters for micro-computed tomography scans of fish otoliths. We tested fifteen different combinations to sagittae. The images were scaled to Hounsfield units, and segmented in two distinct volumes-of-interest (external and internal). The strategy we applied, for identifying optimum scan settings for otoliths, included analyses of the sinogram, the distribution of the Hounsfield units and the signal-to-noise ratio. Based on these tests, the optimum sets of parameters for the acquisition of tomographic images of sagittal otoilths were 80 kV, 220 microA and 0.5 mm aluminum filter.The method allowed 3D shape analysis, internal and external density distribution, layer-by-layer density segmentation, and a potential objective method to count growth rings in otoliths. It was possible to compare mean densities between species, and we observed a significant difference among them. In addition, there are ontogenic changes, which could be increasing or decreasing the density. In this study, we applied tomography for several otolith analysis, that could be of great interest for future studies in diverse areas that use otoliths as the basic structure of analysis, or represents a new research line called eco-densitometry of otoliths, where tomography could be applied to explore the density within an ecological perspective.